Antiphospholipid antibody: laboratory, pathogenesis and clinical manifestations - T. Ziglioli; S. Cartella; C. Casu; A. Tincani; R. Cattaneo (PAGEPress Publications, 2011)
Antiphospholipid antibodies (aPL) represent a heterogeneous group of antibodies that recognize various antigenic targets including beta2 glycoprotein I (β2GPI), prothrombin (PT), activated protein C, tissue plasminogen activator, plasmin and annexin A2. The most commonly used tests to detect aPL are: lupus anticoagulant (LAC), a functional coagulation assay, anticardiolipin antibody (aCL) and anti-β2GPI antibody (anti-β2GPI), which are enzyme-linked immunoassay (ELISA). Clinically aPL are associated with thrombosis and/or with pregnancy morbidity. Apparently aPL alone are unable to induce thrombotic manifestations, but they increase the risk of vascular events that can occur in the presence of another thrombophilic condition; on the other hand obstetrical manifestations were shown to be associated not only to thrombosis but mainly to a direct antibody effect on the trophoblast.